Kegiatan Ekstrakurikuler Seni Tari Dalam Meningkatkan Minat Peserta Didik Di SMK Negeri 1 Kuok - Delfi Rahmi; Yahyar Erawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to find out extracurricular activities in dance In Increasing Student Interest at SMK Negeri 1 Kuok. The theory that researchers use is extracurricular theory. According to Suryosubroto (2013:287) extracurricular activities are additional activities outside the program structure carried out outside normal class hours in order to enrich and expand students' knowledge and abilities, and interest theory. The definition of interest is also mentioned according to Hidayat (2013 in Pratiwi 2015), is something that originates from feelings in the form of a tendency towards something, giving rise to certain actions or activities. The method used in this research is descriptive analysis, with a qualitative approach. The data collection techniques used in this research are observation, interview and documentation data collection techniques. The results of this research conclude that in extracurricular activities students get more material and time to learn dance. In extracurricular activities, students receive material that is different from the learning they receive in class. Therefore, extracurricular activities play a very important role in increasing students' interest in dance. These activities can increase insight or knowledge in the arts, especially dance. Students' interest in dance extracurricular activities at SMK Negeri 1 Kuok can be seen from the evaluation results of the 15 samples in this study, including all those who took part in dance extracurricular activities expressed interest.